Strategi Guru PAK dan Orang Tua Kristen dalam Mengatasi Kesulitan Belajar Peserta Didik pada Pembelajaran Abad 21 - Gulo, Septiana Christi; Kasse, Yublina (PEADA': Jurnal Pendidikan Kristen, 2023)
Education is currently based on the needs that must be achieved to fulfil the needs and demands of the future. The development of technology and information makes the learning paradigm change. The complexity of learning increases with the appearance of various learning problems and difficulties. The challenge faced by students in 21st-century learning is to face the dynamics of the fast-moving world of education, and continuous synergy to ensure graduates have basic competencies that follow the needs of the times. Students who do not keep up with existing developments will find learning difficult in the learning era 4.0. The purpose of the research is to explain how the strategies of PAK teachers and parents are involved in overcoming the difficulties students face in achieving the complexity of learning outcomes in Learning 4.0. In completing this research, the authors used a qualitative method with a literature study approach. with The hope is that the results will provide direction to PAK teachers in teaching effectively, parents, and strategies for educating and assisting their children as they need amid students’ difficulties in keeping up with the change in the development of science which are the demands of 21st-century learning.